VISUAL SEMIOTICS AS A HUMAN-CENTRED COMMUNICATION TOOL IN THE INDIAN SOCIO-CULTURAL CONTEXT - Jha, Aditi (International Journal of Research -GRANTHAALAYAH, 2025)
India is a nation where communication is deeply embedded in visual and symbolic traditions, from religious iconography and folk art to contemporary advertising and digital media. Visual semiotics—the study of signs and meanings—offers a powerful framework for understanding how these visual codes shape human-centred communication in Indian society. This paper examines the role of visual semiotics in designing communication that is empathetic, culturally resonant, and socially inclusive. Drawing on semiotic theory, human-centred design principles, and Indian case studies, the study employs a qualitative methodology combining semiotic analysis, ethnographic interviews with designers, and critical review of public campaigns and branding strategies. Findings highlight how Indian semiotic codes—such as motifs from Madhubani and Warli art, religious symbols like the lotus and Om, and cultural icons like Gandhi’s spectacles—function as tools for building trust, inclusivity, and national identity. The study argues that integrating indigenous semiotic frameworks with human-centred design fosters more impactful and culturally grounded communication strategies for India’s diverse society.